The dissemination of English philosophical works in Spain via translations: The case of Siro García del Mazo’s 'Fundamentos de la moral' (1881) from 'The Data of Ethics' (1879) by Herbert Spencer. - Ramírez-Arlandi, Juan (Universitat de València, 2017)
The dissemination of English philosophical literature in Spain during the last quarter of the nineteenth century calls for an in-depth study of some of the works of Herbert Spencer. His most radical views were recognised by an elite group of Spanish intellectuals who translated his works shortly after the original publication in order to introduce these ideas into the Spanish context. Accordingly, this paper examines the translation of Fundamentos de la moral (1881) rendered by Siro García del Mazo from Spencer’s The Data of Ethics (1879) so as to provide–from a descriptive point of view–a thorough critical revision and analysis of a representative philosophical work from the late nineteenth century
La divulgación de obras de filosofía inglesas en España a través de sus traducciones: El caso de 'Fundamentos de la moral' (1881) de Siro García del Mazo a partir de 'The Data of Ethics' (1879) de Herbert Spencer
Keywords: Filosofía - Gran Bretaña; Spencer, Herbert (1820-1903) - Traducción al español; Siro García del Mazo; Translation of philosophical texts; Norms; Paratexts; Mediation